Pengaruh Profitabilitas dan Likuiditas terhadap Struktur Modal pada Perusahaan Sub Sektor Batu Bara di BEI - Ni Putu Sri Purnami; Gede Putu Agus Jana Susila (Universitas Pendidikan Ganesha, 2021)
This study aims to examine the simultaneous and partial effect of profitability and liquidity on capital structure. The research design used was a causal quantitative design. The subjects in this study are the Coal Sub-Sector which is Listed on the Indonesia Stock Exchange and the objects of research are profitability, liquidity and capital structure. The sampling technique used was purposive sampling with a sample size of 22 companies. Data were collected by recording documents, then analyzed by multiple linear regression analysis. The results showed that (1) profitability and liquidity simultaneously or simultaneously had a significant effect on capital structure with a contribution of influence of 54.4%, (2) profitability had a positive and significant effect on capital structure with a contribution of influence of 32.4%, (3) liquidity has a negative and significant effect on the capital structure with an impact contribution of 36%.